Самоактуалізація у професійному розвитку правоохоронця - Макаренко, П. В.; Makarenko, P. V. (Вісник Національного університету оборони України. - 2014. - Вип. 5(42). - С. 280-284, 2014)
У статті проведено огляд теоретичних досліджень самоактуалізації як багатовимірної величини, що детермінує професійний розвиток особистості. Представлені результати емпіричного дослідження відбивають особливості самоактуалізації правоохоронців які працюють у підрозділах карного розшуку, громадської безпеки та управлінні кадрового забезпечення. Визначено рівень самоактуалізації правоохоронців з різним стажем несення служби в органах внутрішніх справ.

This article provides an overview of theoretical studies of self as a multidimensional value that determines the professional development of the individual. There is showed, that self-actualized personality seeks highly effective work to find new ways, means and resources of quality performance activities while opening their own abilities and developing in all spheres of life (profession, family, friendships, hobbies). That seeking for selfactualization helps to combine professional and personal lives, which is necessary for a balanced personal and professional development. The results of empirical research reflect the features of self-actualization law enforcement officers working in departments of criminal investigation, public security and management staffing. The level of self-actualization police officers from different experience of service in law enforcement agencies.

В статье проведен обзор теоретических исследований самоактуализации как многомерной величины, которая детерминирует профессиональное развитие личности. Представлены результаты эмпирического исследования отражают особенности самоактуализации правоохранителей работающих в подразделениях уголовного розыска, общественной безопасности и управления кадрового обеспечения. Определен уровень самоактуализации правоохранителей с разным стажем несения службы в органах внутренних дел.
Self-actualization in the professional development of law enforcement officers
Keywords: самоактуалізація; правоохоронець; професійний розвиток; self-actualization; law enforcement; professional development; police officers; самоактуализация; правоохранитель; профессиональное развитие